Constructing a methodological approach to examine the determinants affecting purchase intention through perceived risk in the hotel context - Loh, E. G. Y. *; Stephenson, M. L. *; Nezakati, H. * (JMMCB, 2021)
Purchase intention is one of the most widely studied areas in relation to the analysis of consumer markets due to the constantly changing micro and macro environments surrounding businesses. This study aims to provide hotel stakeholders with an understanding on the factors which affect purchase intention. A methodological approach is constructed to examine the effect of leniency of hospitality service policies, e-servicescape and price sensitivity, and the moderating role of perceived risk on purchase intention in the online hotel booking context. The analysis of data will be carried out using Statistical Package for Social Sciences, particularly focusing on factor analysis, regression analysis and descriptive statistics. This study is expected to contribute to the field of marketing in the hotel context, where managers of accommodation establishments would be able to improve brand strategies to appeal to a new wave of customers.